Covalent bonding of the extruded polystyrene foams to mortar through ultraviolet-ozone irradiation. (28th March 2022) - Jin, Xiaodong; Cui, Suping; Zhang, Yao; Zhao, Xinxin; Lv, Feng; Sun, Shibing; Tian, Yingliang; Zhao, Zhiyong; Liu, Donghua
Highlights: The construction of inherent reactive XPSF surface by ultraviolet-zone. The fabrication of covalently bonded XPSF/mortar interfaces. The thorough investigation of the reactions between APTES and XPSF surface. Abstract: The inert surface of extruded polystyrene foams (XPSF) was activated by ultraviolet-ozone (UVO) for the first time to improve the interfacial compatibility with mortar. From the structural analysis (X-ray photoelectron spectroscopic (XPS) and contact angle (CA)), it was suggested that a 10 min UVO exposure was efficient enough to introduce oxygen-contained elements (such as carboxyl groups) upon the obtained UVO-XPSF surface, leading to the increased bonding strength (BS) from 0.058 MPa of neat XPSF/mortar composites to 0.088 MPa. Then, 3-aminopropyl triethoxysilane (APTES) was selected as the promoter to further enhance the BS value of XPSF/mortar composites. The presence of the silane was confirmed by CA, Fourier transform infrared-attenuated total reflection (FTIR-ATR) and XPS. By optimizing the reaction conditions (activation and reaction time: 7 and 3 min, concentration of APTES: 2% and pH value of the silane solution: 10), a maximum BS of 0.168 MPa could be obtained. Through the mechanism analysis, it was demonstrated that APTES acted as a chemical bridge that covalently jointed XPSF by the formation of amide peptide and inorganic mortar by the condensation of silanols.